Diverse and creative voices : theological essays from the majority world - Noelliste, Dieumeme; Chung, Sung Wook, 1966- (Pickwick Publications, 2015)
As the twentieth century passed its midpoint and was rushing toward its end, a growing number of Majority World theologians came to realize that they could in fact do theology in their own contexts for the benefit of their own people. Thus, from the 1960s onward, theologians in the global South have embarked on a form of theological construction that has sometimes been described as "contextual" reflection or "contextualized theology." This volume is motivated by the conviction that these efforts have resulted in theological work that is also beneficial for Christians in other parts of the world. The editors have invited Majority World theologians to share their reflections on several themes of Christian faith from their own sociohistorical perspectives but with an unswerving commitment to the authority of Scripture. It is hoped that these fresh reflections will help Christians in the West engage and benefit from the perspectives of fellow believers in the global South.